Increased transmission potential of Leishmania major/Leishmania infantum hybrids - Volf, Petr; Benkova, Ivana; Myskova, Jitka; Sadlova, Jovana; Campino, Lenea; Ravel, Christophe (International journal for parasitology, 2007)
Development of Leishmania infantum/Leishmania major hybrids was studied in two sand fly species. In Phlebotomus papatasi, which supported development of L. major but not L. infantum, the hybrids produced heavy late-stage infections with high numbers of metacyclic promastigotes. In the permissive vector Lutzomyia longipalpis, all Leishmania strains included in this study developed well. Hybrids were found to express L. major lipophosphoglycan, apparently enabling them to survive in P. papatasi midgut. The genetic exchange of the hybrids thus appeared to have enhanced their transmission potential and fitness. A potentially serious consequence is the future spread of the hybrids using this peridomestic and antropophilic vector.
Keywords: ženské pohlaví; Female; Phlebotomus; Animals; Leishmania major; Leishmania infantum; Crosses, Genetic; zvířata; Psychodidae; křížení genetické